1993
DOI: 10.2190/th88-1w6u-b0at-377u
|View full text |Cite
|
Sign up to set email alerts
|

Race, Gender, and the Effect of Social Supports on the Use of Health Services by Elderly Individuals

Abstract: This study examines the effects of social supports on the use of health services by elderly individuals, and whether those effects differ by race or gender. Multiple regression analysis of the 5,151 baseline Longitudinal Study on Aging (LSOA) respondents revealed that social supports, mainly church attendance, increased the R2s when estimated separately within race and gender groups in a statistically significant manner. The magnitude of these increases, however, was small suggesting that their unique contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
3

Year Published

1995
1995
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 33 publications
3
14
3
Order By: Relevance
“…O n the other hand, Beekm an (1995) found that older individuals very often express depressive feelings in term s of physical sym ptom s. T hirdly, to report sym ptom s in a survey when one is asked to help reserch by doing so, is not the sam e thing as going to a physician to state the sam e sym ptom s. We do not know to what extent the respondents experienced anxiety in connection to their reported sym ptom s. T hat is, the perception of sym ptom s is one, but not the only reason, why people visit health care physicians. For exam ple, the degree of anxiety over the sym ptom s, the degree and quality of social support (Nelson, 1993;Schm itz et al, 1997) and the trust in the health care could be determ ining factors, w hich were not present in the assessm ents of this study.…”
Section: Discussionmentioning
confidence: 73%
“…O n the other hand, Beekm an (1995) found that older individuals very often express depressive feelings in term s of physical sym ptom s. T hirdly, to report sym ptom s in a survey when one is asked to help reserch by doing so, is not the sam e thing as going to a physician to state the sam e sym ptom s. We do not know to what extent the respondents experienced anxiety in connection to their reported sym ptom s. T hat is, the perception of sym ptom s is one, but not the only reason, why people visit health care physicians. For exam ple, the degree of anxiety over the sym ptom s, the degree and quality of social support (Nelson, 1993;Schm itz et al, 1997) and the trust in the health care could be determ ining factors, w hich were not present in the assessm ents of this study.…”
Section: Discussionmentioning
confidence: 73%
“…These findings are generally consistent with previous cross-sectional studies of elderly adults' use of health services that report low R 2 and also indicate that the net contribution of need characteristics is larger than the individual contributions of either the predisposing or enabling characteristics. 16,[32][33][34] . However, using longitudinal data that include the previous use and previous health conditions increased the amount of variance explained by the health care services utilization framework developed by Andersen et al 35 Therefore, one limitation of this study is the crosssectional survey design used.…”
Section: Resultsmentioning
confidence: 99%
“…Portes & Stepick (1993) go further to state that, "common meaning are arrived at when relevant audiences agree to stress certain aspects of a given phenomenon and interpret them on the basis of shared past experience" (Portes & Stepick, 1993: 9). However, projected increases in the cultural diversity of the elder population will have important implications for the provision of health and social services (Nelson, 1993;Angel & Hogan, 1992; U.S. Bureau of the Census, 1992; U.S. G.A.O., 1992;Kravitz, et al, 1989;Wolinsky & Arnold, 1988). Thus, an understanding of the unique factors and determinants that influence the health care utilization behavior of racial/ethnic groups of elders has broader connotations beyond just an academic pursuit.…”
Section: Lillymentioning
confidence: 99%
“…Nelson (1993) states that "social supports play a significant role in the lives of elderly individuals." In other research it has been found that "supportive relationship [s] are associated with lower illness rates, faster recovery rates and higher levels of health care behavior" (Nelson, 1993). For instance, "widowhood significantly alters both eating behaviors and dietary quality" for the worse (Rosenbloom & Whittington, 1993).…”
Section: Elder Populationmentioning
confidence: 99%
See 1 more Smart Citation